Down Regulation of RASSF1a, APC and GSTP1 is Associated with Epithelial Ovarian Carcinoma Tumorigenesis - S, Sandeep Kumar; Swamy, Shalini N; S, Premalatha C; R, Pallavi V; Gawari, Ramesh (Archives of Clinical and Biomedical Research, 2020)
Ovarian cancer is the third leading gynecological malignancy in India with a high mortality rate. The high mortality of the disease is attributed to the late stage diagnosis of the disease. Silencing or down regulation of Tumor Suppressor genes is known to be an early event during tumorigenesis and is known to regulate several cellular events including DNA damage, proliferation and apoptosis. In this study, we have evaluated the mRNA expression of three TSG-RASSF1a, APC and GSTP1 in ovarian carcinoma tissues. We report here that 72/76 samples (94.73%) samples show a down regulation of RASSF1a gene, 47/76 (61.84%) sample show down regulation of APC and 51/76 (67.10%) samples showed down regulation of GSTP1. 100% of the benign samples showed downregulation of RASSF1a and GSTP1 and 77.77% of benign samples showed downregulation of APC gene, which indicates that the down regulation of these TSGs happen early in tumorigenesis and contribute to disease progression.